Carcass characteristics of feedlot-finished Nellore heifers slaughtered at different weights (Acta Scientiarum. Animal Sciences, 2019)
Carcass and meat characteristics of 48 Nellore heifers at 24 to 30 months of age, with an initial weight of 263.4 ± 13.9 kg, were evaluated. The experiment was set up as a completely randomized design with four treatments, which consisted of four slaughter-weight classes, namely 400 kg. Back fat thickness was not influenced (p > 0.05) by slaughter weight in any of the forms it was expressed (mm or %), averaging 5.3 mm. Loin eye area in cm2 increased (p < 0.05) with the increase in slaughter weight. Animals slaughtered at a live weight (LW) of more than 400 kg showed better (p < 0.05) carcass conformation than the other experimental groups (9.8 points). Heifers slaughtered at over 400 kg LW had a more compact (p < 0.05) carcass (1.65 cm kg-1 cold carcass). The marbling degree of meat was lower (p < 0.05) in the animals slaughtered at less than 340 kg LW. In conclusion, cull heifers must not be slaughtered at a LW of less than 340 kg and slaughter weights greater than 400 kg have positive implications on important carcass characteristics, notably conformation and marbling.